(untitled) (The International Journal for Scientific Research, 2025)
This study was conducted to evaluate a production process at Al-Ez Gypsum Factory, owned by Bayot Al-Ez Company, and the extent to which quality is achieved in products that lead to increased competitiveness and market share. This was done by using variable maps to evaluate the production process and data obtained from laboratory tests. The results were analyzed using Minitab.19 statistical software to study the regularity of the production process and its conformity to specifications, and to compare the production process during two periods, 2019-2024. The results obtained from the current phase (2024) in the tests (heat loss, setting time, purity, setting time indicated by the disk) showed that the production process is under control, with a slight dispersion of samples from the centerline observed. When compared with the results of the previous phase (2019), the results showed that the production process during the current period is more stable and under control than the previous production process of 2019, due to the absence of samples outside the control limits and a lower dispersion rate for all laboratory tests.